Socio-Economic Impact of Some Muslim Non-Indigenes on the Development of Karmo Community in Abuja, Federal Capital Territory (FCT), Nigeria - Abdulrahman Yahaya (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
This paper offers an observation at socio-economic impact of some Muslim non-indigenes on the development of Karmo community in Abuja, Federal Capital Territory. It is suggested that the proximity of this community to Abuja could be one of the factors that attracted some non-indigenes including Muslims to take advantage of residing among its natives for decades in the place. The paper highlights different non-indigene tribes of Nigeria who are also located in the community apart from Muslims. It attempts to reveal variant socio-economic impacts that some non-indigenes particularly Muslims are contributing to the growth and development of this community that ranges from the tailoring work, transportation services, trading works, Mai-shayi tea spots and establishment of Islamic centres among others. It examines the development of Karmo community through these aforementioned processes by some Muslim non-indigenes since their settlement. This research employs survey method which data were collected through the in-depth interview technique along with the complementary of literary source materials for its compilation. Finally, the paper concludes by proffering some recommendations that will foster the economic growth and development of people in community as a whole.